An Empirical Analysis on the Relationship between Logistics industry and Economic development of Henan Province - Yu-ping Chu; Jie-jie Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In view of modern logistics industry in economic development playing an increasingly important role, in order to explore the relationship between logistics industry and economic development of Henan province, this paper selects its relevant data of 1990-2010, establishing econometric model, quantitatively studying the relationship between economic development and its logistics industry, in the end we draw conclusions with logistics industry leading to a significant contribution to the economic development of Henan Province.  According to the conclusion, we can be more effective in considering the status of logistics industry in the economic development of the Henan Province, providing basis which related with decisions making for logistics policy. Finally, we make corresponding suggestions according to the conclusions. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2067